RIGID-FLEXIBLE COUPLING DYNAMIC STRESS AND FATIGUE ANALYSIS OF DRIVING WHEELS UNDER TYPICAL WORKING CONDITIONS (MT) - YAN BiJuan; ZHANG HeFeng; WANG ZhiXia; KOU BaoFu; WU FengBiao (Jixie qiangdu)
In order to solve the problem that the driving wheel teeth are easy to break in the harsh working environment, this paper used RecurDyn software to establish the virtual prototype model of the driving wheel crawler mechanism with different number of teeth, and used the finite element software WorkBench to make the driving wheel teeth flexible, and established the rigid-flexible coupling model with the driving wheel teeth as the flexible body. Under the typical working conditions of the Spreader, the driving wheel was simulated, and the contact load between the driving wheel and the crawler shoe and the stress nephogram of the driving wheel teeth with different number of teeth are obtained. On this basis, the fatigue life of the nine tooth driving wheel teeth was analyzed. The results show that: with the increase of the number of driving wheel teeth, the maximum stress in the root area of the driving wheel teeth will decrease; the root area of the driving wheel teeth is the weakest position of the teeth, and the fatigue life is the shortest under the steering condition. The research results provide the basis for the design optimization of the driving wheel.